Perception of Undergraduates About Agricultural Extension Education and Agricultural Development Linkage in Nigeria - Abanigbe, Samuel; Orowole, Paul; Ishola, Jelili (Richtmann Publishing, 2012)
This paper examines the perception of undergraduates toward Agricultural Extension Education (AEE) and Agricultural Development linkage in Nigeria. 188 agricultural students in College of Agriculture, Olabisi Onabanjo University, Aiyetoro, Ogun State and School of Agriculture, Lagos State Polytechnic, Ikorodu were used for the study using percentage, mean score, standard deviation and t-test to analysis data obtained through a questionnaire that was validated by Agricultural extension experts. Result from the study showed that 62.8% of students were male and community was most influencing factor considered in choosing agriculture. 38.3% of respondents perceive AEE as means of developing agriculture. Result also shows that training in agricultural extension (M=2.83) would increase farm output and national income. At 95% confidence interval (p<0.005), there is significance relationships in the students’ perception towards AEE as they agreed that training in extension leads to transformation in agriculture. It is recommended that, there is need for pragmatic youth development and educational programmes of extension for food security and development of agriculture in Nigeria.